Das Herbarium Göttingen, 1832-1852 Akteure, Praktiken, Wissensformate - Ahrens, Frauke Johanna (Universitätsverlag Göttingen, 2020)
In this cultural anthropological examination Frauke Johanna Ahrens enquires into the scientific significance of the herbarium sheets of the Herbarium Göttingen in the period from 1832 to 1852. Based on a historical, object-focused ethnography and praxeology she itemizes how during the establishing phase of the collection institutionalized in 1832 the scientific practices and epistemic interests mutually influenced one another and found expression in the botanical specimens themselves. Each of the five chapters is dedicated to one practice - opening up the collection, ascribing values, acquiring plant material, doing research on herbarium sheets and teaching with herbarium sheets. Together with detailed object descriptions, the analysis emphasizes the materiality of knowledge in this way.